Pengaruh Limbah Cair Tahu Terhadap Pertumbuhan Selada (Lactuca sativa L.) Secara Hidroponik Wick System - Martha Amalia; Iqbar Iqbar; Essy Harnelly (Jurnal Bioleuser, 2024)
Research on the Effect of Tofu Liquid Waste (TLW) on Lettuce (Lactuca sativa L.) growth using the Wick System Hydroponic has been conducted. This research began from October 2019 to June 2020 and was carried out in the Food Education Shelter of Aceh Government Food Service (NAKASIPAN). This research aimed to determine the potential of TLW as a hydroponic medium for lettuce and determine the appropriate concentration for growing media. The study began from October to June 2020 and was carried out at the Aceh Government Food Education Shelter Food Office (NAKASIPAN). The purpose of this study was to determine the potential of TLW as a hydroponic medium for lettuce and determine the appropriate concentration for growing media. This research uses an experimental method using a completely randomized design (CRD). The planting system used the Wick system method, and there were 6 treatments with 4 repetitions, namely P0 (100% water), P1 (100% Ab mix), 100% TLW, 75% TLW, P4 50% TLW, 25% TLW. The results showed that the concentration did not have a significant effect on lettuce plants, as evidenced by the results of further tests of various research parameters. The growth was not significantly different from the control treatment (without liquid tofu waste concentration), but it was significantly different from the treatment using Ab mix 100%. However, this research has proven that liquid tofu waste can be used as a hydroponic medium, but still necessary to find an appropriate concentration for the growth of lettuce plants.